VIBRATIONAL SPECTROSCOPY (FTIR-ATR AND FT-RAMAN) - A Rapid and Useful Tool for Phycocolloid Analysis - Pereira, Leonel (2011)
The wide industrial application of phycocolloids (e.g. alginates, agar and carrageenans) is based on their particular properties to form gels in aqueous solution. Recently, new spectroscopic techniques have provided more accurate identification of the natural composition of the polysaccharides produced by these seaweeds. With the combination of two spectroscopic techniques (FTIR-ATR and FT-Raman) it is possible to identify the principal seaweed colloids in ground seaweed samples as in extracted material. Since the seaweed samples receive the minimum of handling and treatment (e.g. they are simply dried and ground), the composition determined represents, as accurately as possible, the native composition of the phycocolloids.